125 Years of Soil and Crop Management on Sanborn Field: Effects on Soil Physical Properties Related to Soil Erodibility. Issue 5 (May 2017) - Acikgoz, Sebahattin; Anderson, S. H.; Gantzer, C. J.; Thompson, A. L.; Miles, R. J.
Abstract : ABSTRACT: Long-term management systems cause changes to soil physical properties that may affect soil erosion and erodibility. A study was conducted to evaluate the effects of 125 years of continuous crop management on Sanborn Field for selected soil physical properties. Intact soil cores were collected from continuous corn ( Zea mays L.), continuous wheat ( Triticum aestivum L.), continuous timothy ( Phleum pratense L.), and a rotation of corn–wheat–red clover ( Trifolium pratense L.). Soil samples were collected from the surface horizon throughout 1 year (April, July, and November 2014 sampling dates). Aggregate stability, soil splash detachment, bulk density, and soil strength were measured. Significant differences in aggregate stability ( P < 0.01), splash detachment ( P < 0.01), soil shear strength ( P < 0.05), and bulk density ( P < 0.05) were found among the treatments. Continuous timothy had three to four times better aggregate stability and 50% to 75% less splash detachment compared with continuous wheat and corn, respectively. Lowest aggregate stability, lowest soil strength, highest bulk density, and highest soil splash detachment were found under continuous corn. Highest aggregate stability was found during July. Annual crops with tillage have a negative effect on soil quality and erodibility. Comparing results after 125 years with data collected after 105 years illustrates that properties have not changed dramatically during the past 20 years. Assessing the effects of long-term soil management on soil quality and erodibility is critical for society to determine the amount of soil erosion associated with selected soil management and to develop appropriate conservation practices to minimize this challenge and promote long-term sustainability.